1997
DOI: 10.1046/j.1469-8137.1997.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone‐induced accumulation of carbohydrates changes enzyme activities of carbohydrate metabolism in birch leaves

Abstract: SUMMARYBirch cuttings {Betula pendula Roth) were grown in a sand-culture system with two concentrations (0-05, HF and 0-005%, LF) of fertilizer containing macronutrients and micronutrients, and were exposed to 90/40 nll"^ O3 (day/night) and < 3 nl T^ O3 (control) for one growing season in the field fumigation chambers at Birmensdorf (Switzerland). Leaves of different ages were analysed for gas exchange, contents of chlorophyll, protein, and for metabolites as well as enzyme activities of carbohydrate metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 54 publications
5
17
0
Order By: Relevance
“…However, the estimates made here might not be valid since photosynthesis measurements taken from young leaves were used to determine C gain. Ozone tends to decrease chlorophyll levels and photosynthesis in older leaves (Einig et al, 1997), but our estimate was based on the photosynthesis of the first fully expanded leaves, so C gain might be overestimated for plants in the O $ treatments. A study with Plantago major showed that plants may acclimate to O $ with only 14 d of exposure (Lyons & Barnes, 1998).…”
Section: mentioning
confidence: 96%
See 1 more Smart Citation
“…However, the estimates made here might not be valid since photosynthesis measurements taken from young leaves were used to determine C gain. Ozone tends to decrease chlorophyll levels and photosynthesis in older leaves (Einig et al, 1997), but our estimate was based on the photosynthesis of the first fully expanded leaves, so C gain might be overestimated for plants in the O $ treatments. A study with Plantago major showed that plants may acclimate to O $ with only 14 d of exposure (Lyons & Barnes, 1998).…”
Section: mentioning
confidence: 96%
“…Future research should include studies with perennials and woody species. Because other studies have shown both that O $ responses are mediated by nutrient levels (Einig et al, 1997) and that nutrient uptake is affected by root temperature (Hood & Mills, 1994), adding differing nutrient treatments to O $ and root temperature would provide a more thorough understanding of how these factors affect plant growth in the field. …”
Section: mentioning
confidence: 99%
“…The ozone exposure also caused a significant increase in the amount of the soluble sugars in the sensitive line. Ranieri et al (2000) and Einig et al (1997) report accumulation of starch in ozone-fumigated leaves of poplar (Populus deltoides × maximowiczii) clones and birch (Betula pendula), respectively.…”
Section: Carbohydrates and Other Biochemical Measuresmentioning
confidence: 99%
“…1994, Alaoui-Sosse etal. 1996, Einig et al 1997). On the other hand, Kingston-Smith et al (1998) showed that in source leaves of poplar (Populus alba x tremula L.), as well as in other plant species, AI was not directly involved in sucrose degradation.…”
Section: Discussionmentioning
confidence: 94%
“…Sucrose breakdown catalysed by invertase or SuSy is associated with the differential induction of ATP-and PPi-dependent phosphofructokinases (Stitt 1998). The effects of sulphite on catabolic sucrose metabolism are absent in the literature and there are also only a few studies describing sucrolytic activity in source leaves in woody species (Alaoui-Sosse et al 1996, Einig et al 1997, Kingston-Smith et al 1998. Therefore, the question raised in this study is whether disturbances in sucrose synthesis in leaves treated with sulphite are also associated with changes in sucrolytic activities.…”
Section: Introductionmentioning
confidence: 84%